THE DEVELOPMENT OF LECTURE MODEL OF CHEMICAL EDUCATION MANAGEMENT BASED ON LESSON STUDY TO IMPROVE CHEMISTRY TEACHER CANDIDATESâ PROFESIONALISM - Sumarti, S.S.; Supardi, K.I.; Sumarni, W.; -, Saptorini (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
The purpose of this research is to produce a lecture model of chemical education management based on lesson study as an effort to improve chemistry teacher candidatesâ professionalism. This study used a model of ADDIE (Analysis-Design-Implement-Develop-Evaluate). Based on the results of the reflection, lecturer and team can arrange the post-presentation activities (discussing material theoretically) with a variety of management practices in the field. Activities will be carried out by presenting a real problem in the field to find the solution, thus the studentsâ curiosity about management implementation will be fulfilled. Lecture Model of Chemical Education Management Based on Lesson Study can improve the chemistry teacher candidatesâ professionalism, primarily in preparing, presenting and being responsible of their work by learning from their learning experience.